Comprehensive assessment of emergency departments in county-level public hospitals: a multicenter descriptive cross-sectional study in Henan province, China - Cheng, Yanwei; Cao, Xue; Zhang, Jiange; Xu, Lijun; Qin, Lijie (Frontiers in Public Health, 2023)
Background: Emergency Departments (EDs) play a crucial role in providing immediate medical care, particularly in densely populated countries like China. While previous research has predominantly focused on well-funded urban hospitals, this study offers a comprehensive evaluation of EDs in county-level public hospitals in Henan province, China, aiming to identify disparities and challenges. Methods: A descriptive cross-sectional survey was conducted in 382 public hospitals across Henan province, China, from July 1, 2023, to August 1, 2023. Data were collected using an electronic questionnaire covering hospital information, human resources, infrastructure, clinical capabilities, and operational capacities. The data collection period for this survey spanned from January 1 to December 31, 2022. Results: With a remarkable 94.0% response rate, our study reveals significant disparities in county-level public hospitals compared to their provincial or municipal counterparts in Henan Province, China. County-level hospitals, which constitute 266 of the total 342 surveyed facilities, exhibit notable differences, including fewer doctors (median: 11 vs. 23, p < 0.0001) and nurses (median: 18 vs. 37, p < 0.0001). Additionally, a higher proportion of junior doctors is observed in these hospitals, while senior medical staff are more prevalent in provincial or municipal hospitals (p < 0.001). County-level hospitals also face resource challenges, with fewer beds in the emergency room (median: 4 vs. 7, p = 0.0003) and limited proficiency in advanced clinical procedures such as POCT, fiberoptic bronchoscopy, CRRT, ECMO, ultrasound equipment operation, and intraosseous infusion, with significant differences noted in most of these capabilities (p < 0.05). Operational capabilities show distinctions as well, with county-level hospitals managing a lower patient volume (median: 14,516 vs. 34,703, p < 0.0001) and handling fewer pre-hospital CPR cases (median: 33 vs. 89, p < 0.0001). In-hospital CPR success rates are also lower in county-level hospitals (median ROSC: 25.0% vs. 42.8%, p = 0.0068). Conclusion: While provincial or municipal hospitals enjoy better resources, county-level hospitals, especially crucial in less urbanized regions, face substantial challenges. Addressing these disparities is imperative, necessitating targeted investments, improved infrastructure, enhanced clinical training, and the adoption of innovations like telemedicine to enhance the quality of emergency care.